Evolution of CO2 Uptake Degree of Ordinary Portland Cement During Accelerated Aqueous Mineralisation - Giuseppe Ferrara; Pedro Humbert; Davide Garufi; Paola Palmero (Ceramics)
The utilisation of carbonation treatments to produce building materials is emerging as a valuable strategy to reduce CO2 emissions in the construction sector. It is of great importance to regulate the degree of carbonation when the mineralisation process is combined with hydration, as a high CO2 uptake may impede the development of adequate strength. A significant number of studies focus on attaining the maximum carbonation degree, with minimal attention paid to the examination of the evolution of CO2 uptake over the initial stages of the process. In this context, the present study aims to investigate the evolution of CO2 uptake over time during carbonation. Ordinary Portland Cement (OPC) is employed as material, with aqueous carbonation selected as the mineralisation process. This investigation encompasses a range of carbonation durations, spanning from 5 to 40 min. The analysis of the evolution of the mineral composition with time demonstrated that the rate of the carbonation reaction accelerates in the initial minutes, resulting in the conversion of all the portlandite produced during the hydration process in the initial 10 min. Quantitative analysis of the carbonation degree indicated that the CO2 uptake at 40 min is equal to 19.1%, which is estimated to be approximately 70% of the maximum achievable value. By contributing to the understanding of the early carbonation mechanisms in aqueous conditions of OPC, this study provides valuable support for further investigation focused on the use of cement mineralisation processes to produce building materials.